Migration of diethylhexyl phthalate from PVC bags into intravenous cyclosporine solutions - Gotardo, M. A.; Monteiro, Magali [UNESP] (Elsevier B.V., 2005)
The migration of diethylhexyl phthalate (DEHP) from PVC bags into LVPS (0.9% NaCl) and LVPS with cyclosporine at concentrations of 2.5 and 0.5 mg/ml was studied. PVC bags were placed in contact with these solutions and stored at 25 1 degrees C. They were taken for analysis each 30 min during 6 h and after this period at each 1 h until 12 h of contact. Water was used as reference, and exposed and analyzed under the same conditions. After contact, the solutions were submitted to extraction with hexane and analyzed by GC-FID. The results showed that DEHP did not migrate into water and LVPS during all the time. Also, no measurable amount of DEHP was detected during the first 3 h of contact between the PVC bag and the diluted cyclosporine solution. However, the amount of released DEHP reached a detectable level after 4 It of contact, increased until 6 h, stabilized, and increased again after 9-10 h. The 12 h of contact showed the highest DEHP levels for both cyclosporine concentrations. The DEHP migrated was 0.02-0.08% of that present in the bag. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: migration; diethylhexyl phthalate; PVC bags; cyclosporine; intravenous solutions; gas chromatography